2016
DOI: 10.1016/j.actbio.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

3D silicon doped hydroxyapatite scaffolds decorated with Elastin-like Recombinamers for bone regenerative medicine

Abstract: Abstract.The current study reports on the manufacturing by rapid prototyping technique of threedimensional (3D) scaffolds based on silicon substituted hydroxyapatite with Elastin-like Recombinamers (ELRs) functionalized surfaces. Silicon doped hydroxyapatite (Si-HA), with Ca 10 (PO 4 ) 5.7 (SiO 4 ) 0.3 (OH) 1.7 h 0.3 nominal formula, was surface functionalized with two different types of polymers designed by genetic engineering: ELR-RGD that contain cell attachment specific sequences and ELR-SN A 15/RGD with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…As pointed out above, the ELRs show thermosensitivity, thus meaning that hydrogels, which are stable at body temperature, can be formed whenever the T t of the ELR is lower than this temperature [27]. Several studies have shown how different types of ELRs can be used in some of the most challenging fields of tissue regeneration, such as cardiovascular [28], ocular prosthesis [29] and osteochondral applications [30, 31], among others [27].…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out above, the ELRs show thermosensitivity, thus meaning that hydrogels, which are stable at body temperature, can be formed whenever the T t of the ELR is lower than this temperature [27]. Several studies have shown how different types of ELRs can be used in some of the most challenging fields of tissue regeneration, such as cardiovascular [28], ocular prosthesis [29] and osteochondral applications [30, 31], among others [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, when osteoblast differentiation was evaluated, expression of the osteoblast markers OC and ALP demonstrated that the Si-HA-SNA15containing scaffolds were very efficient at leading the rBMSCs into the osteoblastic lineage. In summary, we can conclude that although cells were able to grow on and colonize any of the scaffolds tested, their behavior differed and the biochemical signal generated by the functionalized ELR significantly enhanced the osteoconductive properties of the scaffolds [115]. In contrast to bone, some tissues, such as enamel for example, are unable to regenerate.…”
Section: Skeletal System Regenerationmentioning
confidence: 87%
“…However, all cell‐validated attempts were limited to a maximum of 3‐mm total thickness (Chen et al, ; Choi et al, ; Rodda et al, ). A homogenous distribution of bone marrow MSCs on silicon‐substituted hydroxyapatite scaffolds functionalized with elastin‐like recombinamers‐RGD has been achieved, but only on a maximum 2‐mm scaffold thickness (Vila et al, ). Similarly, functionalized polyethylene glycol molecules with cyclic RGD on aerographite produced 3D scaffolds of 3‐mm thickness but did not achieve cellular infiltration further than a depth of 580 μm (Lamprecht et al, ).…”
Section: Discussionmentioning
confidence: 99%